2020
DOI: 10.3390/rs12244104
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Delineation and Height Measurement of Regenerating Conifer Crowns under Leaf-Off Conditions Using UAV Imagery

Abstract: The increasing use of unmanned aerial vehicles (UAV) and high spatial resolution imagery from associated sensors necessitates the continued advancement of efficient means of image processing to ensure these tools are utilized effectively. This is exemplified in the field of forest management, where the extraction of individual tree crown information stands to benefit operational budgets. We explored training a region-based convolutional neural network (Mask R-CNN) to automatically delineate individual tree cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 53 publications
1
23
0
1
Order By: Relevance
“…The main reason is that, due to the diversity of trees in mixed forests, the crown features' variability in remote-sensing images is magnified, which would cause the model to become more difficult to train. This finding is consistent with that of Chadwick (2020), who suggested that accurate tree detection is possible with fine-spatial-resolution imagery and point clouds [45].…”
Section: The Influence Of Forest Type and Disease Outbreak Intensity ...supporting
confidence: 92%
“…The main reason is that, due to the diversity of trees in mixed forests, the crown features' variability in remote-sensing images is magnified, which would cause the model to become more difficult to train. This finding is consistent with that of Chadwick (2020), who suggested that accurate tree detection is possible with fine-spatial-resolution imagery and point clouds [45].…”
Section: The Influence Of Forest Type and Disease Outbreak Intensity ...supporting
confidence: 92%
“…The Mask R-CNN model was trained in ArcGIS API for Python. In order to complete the task, the backbone can be adjusted to learn new features during the transfer learning process [56,57]. In addition, the epoch was set to 100 to train the networks, with a batch size of 4.…”
Section: ) Preparation For the Training Datasetmentioning
confidence: 99%
“…CNN can reproduce expert observations of individual trees over hundreds of hectares and has become a powerful artificial intelligence tool for analyzing forestry RGB images [4]. The widespread use of DL and CNN in forest research has facilitated analysis of tree detection [24], tree species classification [25,26] and forest disturbance detection [27,28] in detail. Specifically, an improved Res-UNet network [29] has been designed to classify tree species in the aerial orthophotos from Nanning peak forests with an accuracy of 87%.…”
Section: Introductionmentioning
confidence: 99%